Comparison Of Conventional And Recycled “Green” Office Paper - Možina, Klemen; Rutar, Vera (Journal of Graphic Engineering and Design, 2023)
To confront with the market need, we have to find alternative in respond to enormous necessity and application of office paper. Therefore, one way in dealing with the problem is to replace or just decrease the use of paper made entirely from primary components, mainly wood fibbers (deciduous and conifer). We analysed mechanical, optical, structural and microscopic properties. Experiments were performed on three conventional and three recycled office papers reachable on the market. Results, obtained from measurements, confirm presumption, that mechanical and surface properties of recycled office paper can be collated and they discern from conventional office paper.